Structure and frictional properties of ultrahard AlMgB14 thin coatings - Tkachev, Dmitriy; Zhukov, Ilya A.; Nikitin, Pavel Yu; Sachkov, Victor Ivanovich; Vorozhtsov, Alexander B. (Nanomaterials)
This paper presents the results of studies on AlMgB14-based ceramic coatings deposited on WC-Co hard alloy substrates using RF plasma sputtering. The aim of this work is to study the structure, phase composition, and mechanical properties of AlMgB14-based coatings depending on the sputtering mode. According to the results of the microstructural study, the bias voltage applied to the substrate during the sputtering process significantly contributed to the formation of the coating morphology. Based on the results of compositional and structural studies by energy dispersive X-ray spectroscopy, X-ray diffraction, and Raman spectroscopy, it was found that the coatings are composed of nanocrystalline B12 icosahedrons distributed in an amorphous matrix consisting of Al, Mg, B, and O elements. The nanohardness of the coatings varied from 24 GPa to 37 GPa. The maximum value of the hardness together with the lowest coefficient of friction (COF) equal to 0.12 and wear resistance of 7.5